Evaluation of Microwave Ablation in 4T1 Breast Tumor by a Novel VEFGR2 Targeted Ultrasound Contrast Agents - Li, Xiaoyu; Xia, Shujun; Ji, Ri; Zhan, Weiwei; Zhou, Wei (Frontiers in Oncology, 2021)
Objectives A novel UCA VEGFR2-targeting iron-doped silica (SiO2) hollow nanosphere (VEGFR2-PEG-HSNs-Fe) was prepared and applied in microwave ablation for breast cancer to investigate its value in the evaluation of effectiveness after tumor ablation Methods VEGFR2-PEG-HSNs-Fe was prepared by using nano-SiO2, which was regarded as a substrate and etched by Ferrous acetate, and then modified with VEGFR2 antibody. Laser confocal microscope and flow cytometry were used to observe its main physicochemical properties, and biological safety was also investigated. After the xenograft tumor of 4T1 cells was treated by microwave ablation, the extent of perfusion defect was evaluated by ultrasound with injecting VEGFR2-PEG-HSNs-Fe. Results The average particle size of VEGFR2-PEG-HSNs-Fe was 276.64±30.31 nm, and the surface potential was -13.46±2.83 mV. In vitro, the intensity of ultrasound signal increased with UCA concentration. Good biosafety performed in vivo and in vitro experiments. The enhanced ultrasound signal was detected in the 4T1 breast tumor after injecting VEGFR2-PEG-HSNs-Fe, covering the whole tumor. The lesions, which were incompletely ablated, presented as contrast agent perfusion at the periphery of the tumor, and CEUS was performed again after complementary ablation. It was confirmed that all the lesions were completely ablated. Conclusion Nano-targeted UCA VEGFR2-PEG-HSNs-Fe had good biosafety and ability of specific imaging, which might be used as a contrast agent in CEUS to evaluate the efficacy of tumor ablation.